Hemorrhagic disseminated intravascular coagulation after 177Lu-Dotatate in metastatic midgut neuroendocrine tumor: A case report. Issue 40 (8th October 2021) - Worbe, Noémie; Damian, Louise; Le Cam-Duchez, Véronique; Levesque, Hervé; Michel, Pierre; Quak, Elske
Abstract: Rationale: Peptide receptor radionuclide therapy with 177 Lu-Dotatate represents a major breakthrough in the treatment of metastatic well differentiated neuroendocrine tumors. This treatment is generally well tolerated. Reported severe long-term hematological side effects are rare and include hematopoietic neoplasms and bone marrow failure. Patients concerns: We describe the case of a patient presenting spontaneous bleeding and bruising occurring 6 weeks after the first administration of 177 Lu-Dotatate. Blood tests showed anemia, thrombocytopenia, prolonged clotting times, profound fibrinolysis and low levels of coagulation factors II and V. There were no signs of tumor lysis syndrome. Diagnoses: We made the diagnosis of acute disseminated intravascular coagulation. Intervention: Treatment consisted of multiple transfusions of fresh frozen plasma, fibrinogen and platelets, and corticosteroids. Acute disseminated intravascular coagulation (DIC) persisted for 10 days and then resolved. Outcomes: Metabolic imaging 5 months after the 177 Lu-Dotatate administration showed disease progression. Treatment with 177Lu-Dotatate was not rechallenged due to the occurrence of DIC. Lessons: Our case suggests that acute hemorrhagic disseminated intravascular coagulation can be a rare and life-threatening subacute side effect of 177 Lu-Dotatate peptide receptor radionuclide therapy.